Foundations for the Development of Creative Thinking in Younger Schoolchildren as A Psychological and Pedagogical Problem - Qo'chqarova Mahmuda Adxamjonovna; Nazirova Sevara Bahtiyorjon qizi (Peerian Journals Publishing, 2023)
This article examines foundations for the development of creative thinking in younger schoolchildren as a psychological and pedagogical problem
Keywords: Pedagogical impact; teacher-student relationship; emotional aspect